Turbulent droplet breakage probability: Analysis of fitting parameters for two commonly used models. (2nd February 2023) - Ravichandar, Krishnamurthy; Olsen, Michael G.; Dennis Vigil, R.
Highlights: The most widely used drop breakage models require parameter fitting. Explicit expressions were derived for breakage probability parameters. Experimental data was used to validate these new expressions. A von Kármán box was used for some experiments. Abstract: Droplet breakage in liquid–liquid systems is an important physical process in manufacturing operations throughout the chemical, food, and pharmaceutical industries. Although several mathematical models have been developed to describe droplet breakage in agitated liquid emulsions, the utility of these models is limited by the fact that they incorporate multiple fitting parameters that must be determined empirically for specified fluid pairs and flow conditions. In this work, analytical expressions that can be evaluated without need to perform droplet breakage experiments have been developed for parameters associated with droplet breakage probability in two commonly used breakage models. These expressions were derived by applying dimensional analysis and by using a hypothesis regarding breakage probability that is based upon competition between disruptive and restorative stresses on droplets. Data used for validation of the proposed equations for the breakage probability parameters were obtained from previously published reports of droplet breakage in heterogeneous flow devices, as well as from experiments performed in a von Kármán box designed to produce homogeneous turbulence. Comparison of the droplet breakage probability predictions using the derived expressions for the breakage parameters show generally good agreement with experimental data.